Social responsibility of chemical industry enterprises - Tetřevová, Liběna (University of Pardubice, 2013)
The paper is dedicated to the problems of corporate social responsibility from the point of view of chemical industry enterprises. Social responsibility of chemical industry enterprises represents, with respect to the specific safety risks of this industry, an important factor of their success, growth and development. The paper aims to identify, on the basis of the theoretical background of corporate social responsibility, the key areas and possible activities of corporate socially responsible behaviour in the chemical industry. The paper defines the term of corporate social responsibility and compares alternative areas and activities of socially responsible behaviour of enterprises. The given problems are then discussed from the point of view of chemical industry enterprises.